2017
DOI: 10.1016/j.celrep.2017.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Caspase-10 Negatively Regulates Caspase-8-Mediated Cell Death, Switching the Response to CD95L in Favor of NF-κB Activation and Cell Survival

Abstract: SummaryFormation of the death-inducing signaling complex (DISC) initiates extrinsic apoptosis. Caspase-8 and its regulator cFLIP control death signaling by binding to death-receptor-bound FADD. By elucidating the function of the caspase-8 homolog, caspase-10, we discover that caspase-10 negatively regulates caspase-8-mediated cell death. Significantly, we reveal that caspase-10 reduces DISC association and activation of caspase-8. Furthermore, we extend our co-operative/hierarchical binding model of caspase-8/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
54
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(63 citation statements)
references
References 52 publications
8
54
0
1
Order By: Relevance
“…However, at later timepoints (180 min), there were detectable, albeit low, levels of FLIP (L) at the DISC in CASP8 null cells, approximately half of which was in its unprocessed p55-form ( Fig 3A; lane 6). In agreement with the findings of others for the Fas/CD95 DISC [30], recruitment of procaspase-8's other paralog, procaspase-10, to the TRAIL-R2 DISC was also inhibited in the absence of procaspase-8; however, low amounts were again detectable at the latest timepoint. In isogenic HCT116 models lacking either procaspase-8, procaspase-10, or both, we further confirmed the importance of procaspase-8 for both FLIP and procaspase-10 recruitment (Figs 3B and EV5B).…”
Section: Flip(l) Inhibits Full Caspase-8 Activation When Equistoichiosupporting
confidence: 92%
“…However, at later timepoints (180 min), there were detectable, albeit low, levels of FLIP (L) at the DISC in CASP8 null cells, approximately half of which was in its unprocessed p55-form ( Fig 3A; lane 6). In agreement with the findings of others for the Fas/CD95 DISC [30], recruitment of procaspase-8's other paralog, procaspase-10, to the TRAIL-R2 DISC was also inhibited in the absence of procaspase-8; however, low amounts were again detectable at the latest timepoint. In isogenic HCT116 models lacking either procaspase-8, procaspase-10, or both, we further confirmed the importance of procaspase-8 for both FLIP and procaspase-10 recruitment (Figs 3B and EV5B).…”
Section: Flip(l) Inhibits Full Caspase-8 Activation When Equistoichiosupporting
confidence: 92%
“…This has been confirmed in our lab using several CRISPR/Cas9 caspase‐8 knockout lines (D. B. Longley, unpublished observations). Interestingly, caspase‐10 has been recently shown to inhibit caspase‐8 activation, supporting earlier research that reported that the caspase‐8/‐10 heterodimer is inactive . Therefore, in overexpression models, caspase‐10 can induce cell death, whereas at physiologically relevant expression levels, it seems to inhibit caspase‐8‐mediated apoptosis.…”
Section: Canonical Flip Biology: Regulation Of Caspase‐8 Activationsupporting
confidence: 70%
“…It is noteworthy that the murine gene for caspase‐10 is a pseudogene—raising questions about the physiological role of the human counterpart. Whether caspase‐10 can induce apoptosis in the absence of caspase‐8 is subject to debate, and one recent study even suggested that caspase‐10 has a potential inhibitory role (similar to that of FLIP) . In some cell types, the amount of active caspases‐8 and ‐10 is too low to directly activate the downstream executioner caspases (caspases‐3, ‐6 and ‐7).…”
Section: Lymphocyte Apoptosis: Extrinsic Versus Intrinsic Pathwaysmentioning
confidence: 99%